2023
DOI: 10.1186/s12913-023-10462-2
|View full text |Cite
|
Sign up to set email alerts
|

The application of artificial intelligence in health policy: a scoping review

Maryam Ramezani,
Amirhossein Takian,
Ahad Bakhtiari
et al.

Abstract: Background Policymakers require precise and in-time information to make informed decisions in complex environments such as health systems. Artificial intelligence (AI) is a novel approach that makes collecting and analyzing data in complex systems more accessible. This study highlights recent research on AI’s application and capabilities in health policymaking. Methods We searched PubMed, Scopus, and the Web of Science databases to find relevant st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Additionally, research indicates that artificial intelligence (AI) may enhance the capacity of public health to advance everyone’s health in every community [ 16 , 17 ]. Public health organizations must carefully consider their AI implementation techniques in order to properly fulfill this promise and apply AI to public health tasks [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research indicates that artificial intelligence (AI) may enhance the capacity of public health to advance everyone’s health in every community [ 16 , 17 ]. Public health organizations must carefully consider their AI implementation techniques in order to properly fulfill this promise and apply AI to public health tasks [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deployment of LLMs in health communication, particularly its ability to be detect public concerns early and inform communication, is an important opportunity 15. AI’s precision and capacity to replicate the desired tone positions it as a pivotal player in public health messaging; it can deliver clear, concise, and contextually relevant information.…”
Section: Ai’s Role In Addressing Vaccine Hesitancymentioning
confidence: 99%
“…The deployment of LLMs in health communication, particularly its ability to be detect public concerns early and inform communication, is an important opportunity. 15 AI’s precision and capacity to replicate the desired tone positions it as a pivotal player in public health messaging; it can deliver clear, concise, and contextually relevant information. Some research has found that patients sometimes prefer AI generated messages as they have a more empathetic tone than doctors, 16 although one systematic review found that public opinion on AI in healthcare was mixed.…”
Section: Ai’s Role In Addressing Vaccine Hesitancymentioning
confidence: 99%
“…These advantages for patients include gaining a deeper understanding of their medical conditions through research conducted in artificial intelligence programs, as well as engaging in interactive conversations by posing questions in a natural conversational manner, which they might not have had the opportunity to ask their doctors. Additionally, patients benefit from effectively managing their treatment through features like drug reminders, self-monitoring, dosage guidance, and accessing information on the potential side effects of therapy [4][5][6]. On the other hand, healthcare professionals benefit from utilizing artificial intelligence in the process of diagnostic radiology and medical education, as well as in the planning, execution, and composition of medical research within the field [7,8].…”
Section: Introductionmentioning
confidence: 99%